Production and Biophysical Characterization of Phi8P4 Helicase - Moura, Siroun (Jihočeská univerzita, 2020)
The goal of this thesis was cloning of Phi8P4 protein into expression vector with N-terminal his-tag, optimization of protein expression and large-scale production for further functional and crystal structure studies with RNA.
Production and Biophysical Characterization of Phi8P4 Helicase
Keywords: dsRNA viruses; bacteriophages; P4 protein; Phi8P4; N-terminal His-tag; dsRNA viruses; bacteriophages; P4 protein; Phi8P4; N-terminal His-tag